Co-firing and shrinkage matching in low- and middle- permittivity dielectric compositions for a low-temperature co-fired ceramics system - Choi, YJ; Park, JH; Ko, WJ; Hwang, IS; Park, JH; Park, JG; Nahm, S (WILEY, 2006)
Co-firing and shrinkage matching of low- and middle- permittivity dielectric compositions for the application to a low-temperature co-fired ceramics system was investigated. Several glass compositions were initially examined for the low-temperature firing of middle-K (K similar to 20) dielectrics, and their compositions were further modified for shrinkage matching between low-K (K similar to 6) and middle-K layers. By controlling the processing parameters such as the solid loading ratio and stacking sequence, the warpages between hetero-layers could be minimized.
Keywords: GLASS ADDITIONS; MICROSTRUCTURE